The Kusamala Program for primary caregivers of children 6–59 months of age hospitalized with severe acute malnutrition in Malawi: study protocol for a cluster-randomized controlled trial - Daniel, Allison I. (Trials, 2017)
BACKGROUND: Severe acute malnutrition (SAM) is associated with high mortality rates and impairments in growth and development in children that do survive. There are complex nutritional, health, and behavioural risk factors involving severely malnourished children and their primary caregivers, requiring integrated intervention approaches. METHODS: A cluster-randomized controlled trial at the Queen Elizabeth Central Hospital in Blantyre, Malawi will be conducted to evaluate the effectiveness of a 4-day hospital-based intervention programme directed at primary caregivers. This programme, titled the Kusamala Program, aims to improve developmental and nutritional outcomes in children with SAM. Up to six primary caregivers and their children will be enrolled to groups each week, which will be randomly allocated to intervention or comparison arms. The intervention package consists of interactive counselling on three modules: 1) nutrition and feeding; 2) water, sanitation, and hygiene (WASH); and 3) psychosocial stimulation. Data collection will be performed at enrolment, at discharge from hospital, and at 6 months following discharge. The primary outcome is child development assessed with the Malawi Developmental Assessment Tool (MDAT), a validated measure of gross and fine motor, language, and social development. DISCUSSION: This intervention programme is unique because it utilizes primary caregivers’ time spent in-hospital while children receive treatment for SAM. The programme has the potential to be effective in addressing multiple aspects of child, nutrition and development. TRIAL REGISTRATION: ClinicalTrials.gov, NCT03072433. Registered on 7 March 2017. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13063-017-2299-3) contains supplementary material, which is available to authorized users.